Simulation of fertilizer requirement for irrigated wheat in Eastern India using the QUEFTS model. (2006) - Maiti, Debtanu; Das, D.K.; Pathak, H.
Abstract : Crop modeling can provide us with information about fertilizer dose to achieve the target yield, crop conditions, etc. Due to conventional and imbalanced fertilizer application, nutrient use efficiency in wheat is low. Estimation of fertilizer requirements based on quantitative approaches can assist in improving yields and nutrient use efficiency. Field experiments were conducted at 20 sites in eastern India (Nadia district of West Bengal) to assess the soil supply, requirement, and internal efficiency of N, P, K, and Zn in wheat. The data were used to calibrate the QUEFTS (Quantitative Evaluation of the Fertility of Tropical Soils) model for site-specific, balanced fertilizer recommendations. The parameters of maximum accumulation (a) and maximum dilution (d) in wheat were calculated for N (35, 100), P (129, 738), K (17, 56), and Zn (21502, 140244). Grain yield of wheat showed statistically significant correlation with N (R 2 = 0.937**), P (R 2 = 0.901**), and K uptake (R 2 = 0.801**). The NPK ratio to produce 1 tonne grain yield of wheat was calculated to be 4.9:1.0:8.9. The relationships between chemical properties and nutrient-supplying capacity of soils were also established. The model was validated using the data from four other experiments. Observed yields with different amounts of N, P, K, and Zn were in good agreement with the predicted values, suggesting that the validated QUEFTS model can be used for site-specific nutrient management of wheat.